Pembangunan Infrastruktur Terhadap Pertumbuhan Ekonomi Provinsi Riau - Fitri Sholawati Ritonga (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2020)
Economic success is measured by indicators of economic growth. To boost economic growth must be supported by infrastructure development. Indonesia is still experiencing a disparity in development between regions. There are still many areas outside Java that are experiencing infrastructure problems. Riau Province which has the potential of resources continues to increase infrastructure development in order to promote economic growth and equalization of development. Infrastructure development in Riau has boosted economic growth, this is seen from riau economic growth that is growing positively and quite significantly.llage, Rural Poverty.